Three-dimensional electroanatomical mapping guidelines for the selection of pacing site to achieve cardiac resynchronization therapy - Hua, Bao-Tong; Pu, Li-Jin; Tian, Xin; Song, Wen-Juan; Li, Hao; Wang, Chao; Shao, Xiao-Xia; Li, Rui; Li, Shu-Min; Li, Zhi-Xuan; Zou, Jun-Hua; Zhao, Ling; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims: There are currently two ways to achieve left ventricular activation in cardiac resynchronization therapy (CRT): left bundle branch area pacing (LBBAP) or coronary venous pacing (CVP). However, the criteria to choose the proper way remains scanty. We aimed to evaluate the feasibility of left ventricular electroanatomical mapping to choose LBBAP or CVP. Methods: A total of 44 patients with heart failure, reduced ejection fraction, left bundle branch block (LBBB) were recruited and the three-dimensional electroanatomical mapping of the left ventricle was be used to accurately assess whether the left bundle branch is blocked and the block level. Patients with true LBBB achieved CRT by LBBAP while patients with pseudo LBBB achieved CRT by CVP. After mean follow-up of 6-month, the QRS duration and transthoracic echocardiography including mechanical synchrony indexes were evaluated. Results: 28 patients with true LBBB received LBBAP while 16 without true LBBB received CVP. The QRS notch were significantly wider in LBBAP than in CVP (51.36 ±10.58 vs. 39.38±17.94, p<0.01). Paced QRS duration after the implantation in LBBAP and CVP was significantly narrower than baseline. Biventricular and intraventricular synchronization were significantly improved than baseline in LBBAP and CVP group while atrialventricular synchronization was significantly improved than baseline only in LBBAP group. Conclusion: For heart failure patients with LBBB who are indicated for CRT, left ventricular electroanatomical mapping before CRT, which determine whether the left bundle branch is blocked or not, is a safe and feasible way to choose LBBAP or CVP.